2001
DOI: 10.2460/ajvr.2001.62.320
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the probability for exceeding a threshold concentration of furosemide at various intervals after intravenous administration in horses

Abstract: Interhorse variability with respect to pharmacokinetics of furosemide will result in misclassification of some horses as being in violation of regulatory concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…2). This finding likely reflects the fact that there is considerable interindivdual variability in the pharmacokinetics of plasma furosemide 1 and the fact that plasma furosemide concentration and urine specific gravity are assessing related but distinct processes; plasma furosemide reflects the distribution and elimination of furosemide, whereas urine specific gravity reflects a physiologic effect of the drug on urine production. These data indicate that although urine specific gravity is significantly lowered by furosemide and that higher concentrations of serum furosemide tended to be found more commonly among horses with lower values of urine specific gravity, measure-ment of urine specific gravity alone would not be a useful test for regulating furosemide use.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…2). This finding likely reflects the fact that there is considerable interindivdual variability in the pharmacokinetics of plasma furosemide 1 and the fact that plasma furosemide concentration and urine specific gravity are assessing related but distinct processes; plasma furosemide reflects the distribution and elimination of furosemide, whereas urine specific gravity reflects a physiologic effect of the drug on urine production. These data indicate that although urine specific gravity is significantly lowered by furosemide and that higher concentrations of serum furosemide tended to be found more commonly among horses with lower values of urine specific gravity, measure-ment of urine specific gravity alone would not be a useful test for regulating furosemide use.…”
mentioning
confidence: 98%
“…1 This variability appears to be present irrespective of the testing methodology used to detect furosemide. 1 The coupled testing of urine specific gravity and serum furosemide concentration has been experimentally determined to decrease the frequency of false violators (unpublished data). These experimental findings, however, were obtained from a small group of horses that had not been exercised.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…R ecently, we reported that the estimated rate of exceeding the threshold for violation of furosemide among horses in which regulations for administration of the drug were adhered to (ie, the expected rate of false-violators, or the number of horses that receive furosemide in accordance with regulations that are falsely classified as being in violation of regulations), using the cut-point of 100 ng of furosemide/ml of serum or plasma, was relatively high. 1 In an effort to improve the accuracy of testing and to reduce the rate of false-violators, some racing jurisdictions (eg, the Texas Racing Commission) couple plasma furosemide testing with measurement of urine specific gravity. Specifically, some racing jurisdictions determine urine specific gravity of selected race entrants immediately after racing.…”
mentioning
confidence: 99%